Analisis Kestabilan Lereng Penambangan Dengan Metode Janbu Menggunakan Software Slide 6.0 Pada Area Pit Barat Tambang Terbuka PT. Allied Indo Coal Jaya, Kota Sawalunto, Sumatera Barat. - Fikhrul Arsyad; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. Based on observations made on the slopes in the pit area east of the open pit PT. Allied Indo Coal Jaya, found rock slope which has a height of 16 meters, slope angle is 74 and has many weak plane structures that can cause landslides. From the results of the research that has been carried out, the rock cohesion value is 0.095 MPa and the value of the friction angle in the rock is 39.11º. In determining the value of the slope safety factor using slide 6.0 software, the value of the slope safety factor in saturated conditions is 1.214; the original condition was 1.357 and the dry condition was 1.483. So it can be concluded that the slope is not safe when the conditions are saturated. For that, it is necessary to make improvements to the slope geometry. The recommended improvement is to change the slope geometry to two slopes thereby increasing the value safety factor initialy 1,214 to be 1,266.Keywords: Slope, failure, cohesion, friction angle, safety factor.